Improving the flame‐retardant property of bottle‐grade PET foam made by reactive foam extrusion. Issue 35 (3rd February 2020) - Bethke, Christian; Goedderz, Daniela; Weber, Lais; Standau, Tobias; Döring, Manfred; Altstädt, Volker
Abstract: Upcycling of low intrinsic viscosity (IV) poly(ethylene terephthalate) (PET) grades, such as bottle‐ or recycled grades, by a reactive foam extrusion process, provides an appropriate alternative to high pricing, high IV grades commonly used for foaming applications. However, the drawback of bottle‐grade PET foams is its flame retardant (FR) performance. In this study, pyromellitic dianhydride was used as a chain extender to foam bottle‐grade PET. The influence of different FRs, containing halogenated (HFR) and four different phosphorous‐based types, on the processability and final foam properties was investigated. HFR showed better processability to achieve proper foams with fine morphology compared to P‐based FRs, where the FR content was adjusted between 2 and 5 wt%. However, HFR exhibited lower FR performance by cone calorimeter testing compared to the P‐based FRs and the commercial reference foam Kerdyn. Nonetheless, all of the FRs can only improve the time to ignition of the neat PET foams while the other values depend on the specific type of FR. In addition, all FR foams have improved mechanical properties more than twice in comparison to the neat PET foam. Abstract : Low intrinsic viscosity (and molecular weight) bottle‐grade poly(ethylene terephthalate) is chemically modified with pyromellitic dianhydride during reactive foam extrusion in order to achieve proper foams for sandwich core applications. The influence of different flame retardants, a halogen, and different phosphorous based types, on processability, foam morphology, burning behavior, and mechanics is investigated.